Attitudes Of Regular Alcohol Drinking Adolescents To Intersubjective Relations And Everyday Life - Georgi Sarov (Journal of Biomedical & Clinical Research, 2014)
It is well known that some psychological features of adolescents as extraversion, risk-taking and impulsivity positively associate with substance abuse. The aim of the study was a description of psychological features of adolescents associated with regular alcohol drinking. We conducted a survey using an original questionnaire, classifying alcohol drinking as regular, social (incidental) and abstinence. The adolescents were asked to evaluate their own patterns of drinking. Of the 903 investigated students (aged 15-19), 169 identified themselves as regular alcohol drinkers (RDA), and 279 – as abstainers (NDA). These two groups were compared statistically in terms of a wide range of self-described psychological features. It was found that RDA were more likely to strive for dominant positioning in intersubjective relations (OR 1.8, 95%CI 1.22-2.65), more likely to avoid academic obligations (OR 1.61, 95%CI 1.08-2.39), and more likely to postpone their duties in everyday life (OR 1.81, 95%CI 1.23-2.67). It seems that regular drinking positively associates with egocentric personality traits and help is needed in personality development that could have a positive secondary effect on alcohol prevention.